The Construction of Resistance in the Lyrics of the Song “Bayar Bayar Bayar” by the Band Sukatani - Ahmad Mubarok; Khaerudin Imawan; Novicky Alban Adiputra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study analyzes the creation of meanings of resistance and social criticism in the lyrics of the song